(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
GPRA is a unique material made up of shredded glass, plastic, rubber, and aluminum particles. Concrete is abundantly used building material on the planet, requiring around 12.6 billion tons of natural resources to produce. All of the elements in concrete are partially or completely replaced by a variety of waste products, such as fly ash, rice husk ash, wheat straw ash, and so on. Rapid urbanization and industrialization around the world has resulted in large amounts of plastic trash and waste tyre rubber being deposited. This trash can be used to lower the coarse aggregate content of concrete when used in the proper conditions. This research work looks at the potential of a novel compound GPRA i.e. (Glass, Plastic, Rubber, Aluminum) as a partial replacement in coarse aggregate. Though there has been enough research on use of waste materials as replacement in concrete structures with an aim to curb pollution levels. This research work aims to utilize properties of waste materials which may give a higher performance than individually using of waste materials and while lowering of various pollution levels with cost effective ways for partial replacement of coarse aggregates in concrete, shredded waste materials for GPRA with sizes ranging from 4.75 to 20 mm will be employed. This investigation will use an M30 design mix with a target mean strength of 42 n/mm2. GPRA will be used to partially replace coarse aggregate in the following percentages: 10%, 30%, and 40%. The C.S., S.T.S., and F.S. of GPRA in hardened concrete has to be compared to the individual replacement of these waste materials.